Motor resonance in left- and right-handers: evidence for effector-independent motor representations - Sartori, Luisa; Begliomini, Chiara; Castiello, Umberto (Frontiers in Human Neuroscience, 2013)
The idea of motor resonance was born at the time that it was demonstrated that cortical and spinal pathways of the motor system are specifically activated during both action-observation and execution. What is not known is if the human action observation-execution matching system simulates actions through motor representations specifically attuned to the laterality of the observed effectors (i.e., effector-dependent representations) or through abstract motor representations unconnected to the observed effector (i.e., effector-independent representations). To answer that question we need to know how the information necessary for motor resonance is represented or integrated within the representation of an effector. Transcranial magnetic stimulation (TMS)-induced motor evoked potentials (MEPs) were thus recorded from the dominant and non-dominant hands of left- and right-handed participants while they observed a left- or a right-handed model grasping an object. The anatomical correspondence between the effector being observed and the observer’s effector classically reported in the literature was confirmed by the MEP response in the dominant hand of participants observing models with their same hand preference. This effect was found in both left- as well as in right-handers. When a broader spectrum of options, such as actions performed by a model with a different hand preference, was instead considered, that correspondence disappeared. Motor resonance was noted in the observer’s dominant effector regardless of the laterality of the hand being observed. This would indicate that there is a more sophisticated mechanism which works to convert someone else’s pattern of movement into the observer’s optimal motor commands and that effector-independent representations specifically modulate motor resonance.